Sentencing Outcomes in 28 Felony Courts, 1985 (United States) - Cunniff, Mark A. ([Verlag nicht ermittelbar], 1987)
The purposes of this study are to describe sentencing outcomes in felony courts for selected serious offenses--homicide, rape, robbery, aggravated assault, burglary, larceny, and drug trafficking--and to establish a statistical series on sentencing outcomes in felony courts throughout the United States. The jurisdictions consist of cities and counties with an average population of 1.1 million. Among the jurisdictions, the sentencing schemes available varied, with both determinate and indeterminate sentencing practices in operation. The study distinguishes between core informational items such as criminal charges, type of sentence imposed and terms of the prison sentence, and optional items such as characteristics of the offense and the defendant, and how the case was processed.